Tensile properties and strain response of Cu-Al Bi-metal tube - Baghdadi, A.H.; Misran, I.S.; Sajuri, Z.; Syarif, J. (Fakulti Kejuruteraan ,UKM,Bangi., 2014)
Recent high price of copper in global market forced the heat, ventilation, and air condition (HVAC) industry players to fi nd alternative materials with relatively lower market price compared to copper such as aluminium for replacement. This study characterizes tensile properties and strain response of new Cu-Al bi-metal tubes i.e. aluminium cladded copper (ACC) and copper cladded aluminium (CCA) in order to look at the possibility of applying the bi-metal tubes in HVAC industries. The result shows that tensile properties of CCA tubes was higher than that of ACC bi-metal tubes in two different strain rates of 1 × 10-3 and 1 × 10-1 sec-1. Also, Strain response refers to the sample elongation at break shows a higher elongation value of CCA samples compared to ACC.